Negativni lom svetlobe - Gnamuš, Jan (Matrika, 2024)
Refraction of light is one of the basic optical phenomena. In all isotropic transparent materials in nature, light refracts positively. Negative refraction of light can be achieved with optical metamaterials, which are artificially created structures made from very small building blocks. This article presents the theory of negative refraction and examples of metamaterial structures.
Keywords: negative refraction; negativni lom; optical metamaterials; optics; optični metamateriali; optika